‘SKIF’ SUPPORT SYSTEM OF DISTANCE EDUCATION ON BASIS OF MOODLE SOFTWARE IN DSTU - Olga A. Zakharova (Advanced Engineering Research, 2011)
‘SKIF’ support system for the educational process developed on the basis of Moodle open source software is considered. The logframe and basic functional system modules – libraries of electronic resources and a distance education module are described.